"Sustainable Inclusive and Intercultural Education" as a Means of Supporting Diversity: The Theoretical Framework of a Pedagogical Proposal - Χατζησωτηρίου, Χριστίνα; Σόρκος, Γεώργιος (Education Sciences, 2022)
As modern schools are characterized by conditions of pluralism of ethnicities, special characteristics and abilities, educational systems are called upon to adjust their priorities in order to provide high quality educational services while ensuring the conditions for equal and socially-just participation. In this sense, inclusive and intercultural education can contribute to the transformation of school education. At the same time, the conditions for the intra-generational and inter-generational satisfaction of the needs of all students in the school processes must be created. What we propose in this article is a combined approach to inclusive and intercultural education from a sustainable perspective. This approach is a pedagogical proposal in support of diversity that will lead to Sustainable Inclusive and Intercultural Education (SIIE) which will aim to benefit all students not only of the present but also of future generations.